Ecosystem services value for water provisioning in the Shule River Basin of northwestern China: Spatial and temporal evolution and drivers from 2000 to 2022 - Peng Shi; Dongmei Zhou; Jing Jiang; Jing Ma; Xiaoyan Zhu; Jun Zhang; Zihe Li; Qinghan Dong (Heliyon)
The economic and social functions of water provision have become increasingly important with the gradual scarcity of water resources due to global change. We assessed the spatial and temporal dynamics of the value of ecosystem water-provisioning services in terms of the monetary value shown in the Shule River Basin from 2000 to 2022 to sustain the structure, functionality, and stability of ecosystems. This provides an important reference for the optimization of ecosystem services in the basin and the scientific allocation of water resources. Furthermore, elucidating the spatial and temporal evolution of ecosystem water-provisioning services in the Shule River Basin and understanding their driving mechanisms are important for local sustainable economic development. Analyses were performed using a Geographic Information System (GIS) platform and a geodetector model. The findings were as follows: (1) The value of ecosystem water-provisioning services (measured in monetary terms) in the Shule River Basin showed a fluctuating but increasing trend from 2000 to 2022. (2) The significant fluctuations in the monetary value of ecosystem services from 2000 to 2006 could be primarily attributed to factors such as low precipitation, high temperatures, population growth, and subsequent urban expansion. Conversely, a continuous upward trend in ecosystem service values (ESV) related to water provisioning, which was attributed to enhancements in land cover and increases in agriculture, forestry, grassland, and water bodies, coupled with increased precipitation, occurred from 2006 to 2022. (3) Different factors had different impacts on the ESV. Following the order of decreasing importance, these were land cover, land-use type, topographic surface (represented by the DEM), precipitation, temperature, population density, and economic activity (represented by nighttime lighting). The spatiotemporal evolution of water-provisioning ecosystem services in the Shule River Basin and its driving mechanisms are important for the sustainable development of the local economy. These research findings can provide valuable references for future water conservation and sustainable utilization in areas facing similar challenges.